2023
DOI: 10.1021/acs.chemmater.2c03074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Surface Chemistry, and Fluorescent Properties of InP Quantum Dots

Abstract: InP quantum dots (QDs) have great potential as emitters for solid-state lighting, lasing, and bioimaging without the inherent toxicity concern of Cd and Pb-based emitters. Indium phosphide's small bandgap and high covalency make it uniquely capable of color-pure fluorescence that can be tuned throughout the visible and lower IR spectrum. Until recently, InP-based QDs consistently underperformed when compared with CdSe-based counterparts. Recent efforts to understand indium phosphide's nonclassical growth mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 144 publications
(418 reference statements)
0
34
0
Order By: Relevance
“…Although III−V semiconductors (e.g., InP) are typically in a zinc-blende structure, alkanoate ligands can hardly pair with surface indium cations. 54,55 This is so because the surface cations on the zinc-blende (100) and (111) polar facets (also wurtzite (0001) and (1011) polar facets) are with a large yet fractional charge (+1.5 and + 0.75), neither of which could be easily neutralized by carboxylate group(s) at the crowded interface. In addition, for their cations (such as indium ions), the coordination mode in lattice is different from that with carboxylates.…”
Section: Pairing Alkanoate Ligands With Low-index Zinc-blende and Wur...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although III−V semiconductors (e.g., InP) are typically in a zinc-blende structure, alkanoate ligands can hardly pair with surface indium cations. 54,55 This is so because the surface cations on the zinc-blende (100) and (111) polar facets (also wurtzite (0001) and (1011) polar facets) are with a large yet fractional charge (+1.5 and + 0.75), neither of which could be easily neutralized by carboxylate group(s) at the crowded interface. In addition, for their cations (such as indium ions), the coordination mode in lattice is different from that with carboxylates.…”
Section: Pairing Alkanoate Ligands With Low-index Zinc-blende and Wur...mentioning
confidence: 99%
“…In addition, for their cations (such as indium ions), the coordination mode in lattice is different from that with carboxylates. 54,55 As a result, growth of III−V semiconductor nanocrystals (e.g., InP ones) was found to be uncompetitive with the nucleation, resulting in a growth bottleneck with common indium alkanoates as the indium precursor and sole ligands. 55,56 To our knowledge, there is no proper facet-ligand pairing for III−V semiconductor nanocrystals reported in the literature, resulting in poorly developed synthetic chemistry.…”
Section: Pairing Alkanoate Ligands With Low-index Zinc-blende and Wur...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their environment-friendly characteristics and tunable emission wavelength, indium phosphide (InP) QDs have gained intensive attention and are expected to be more promising alternative QDs. [7][8][9][10] Nevertheless, In and P are chemically active elements, and traps induced by oxygen can be easily formed in InP-based QDs, leading to some disadvantages in optical properties such as low PL QY, easy photobleaching, serious PL blinking, etc. 11,12 Studies have shown that growing wide band-gap semiconductor shells ZnS and ZnSe onto the InP core is an efficient method to overcome these drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their environment-friendly characteristics and tunable emission wavelength, indium phosphide (InP) QDs have gained intensive attention and are expected to be more promising alternative QDs. 7–10…”
Section: Introductionmentioning
confidence: 99%